Preparation of zinc‐oxide‐free natural rubber nanocomposites using nanostructured magnesium oxide as cure activator. Issue 43 (23rd July 2015) - Roy, Kumarjyoti; Alam, Md. Najib; Mandal, Swapan Kumar; Debnath, Subhas Chandra
ABSTRACT The effect of sol–gel synthesized magnesium oxide (MgO) nanoparticles as cure activator is studied for the first time in the vulcanization of natural rubber (NR) and compared with conventional zinc oxide (ZnO) in terms of cure, mechanical, and thermal properties. The NR vulcanizate with 1 phr (Parts per hundred parts of rubber) nano MgO shows an excellent improvement in the curing characteristics and the value of cure rate index is about 400% greater for NR vulcanizate containing 1 phr nano MgO in comparison to the NR vulcanizate with 5 phr conventional ZnO. Both mechanical and thermal properties of NR vulcanizate are found to be satisfactory in the presence of 1 phr nano MgO as cure activator in comparison to conventional NR vulcanizate. This study shows that only 1 phr nano MgO can successfully replace 5 phr conventional ZnO with better resulting properties in the sulfur vulcanization of NR. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42705.